2012
DOI: 10.1182/blood-2012-04-425009
|View full text |Cite
|
Sign up to set email alerts
|

Mouse natural killer cell development and maturation are differentially regulated by SHIP-1

Abstract: The SH2-containing inositol phosphatase-1 (SHIP-1) is a 5 inositol phosphatase known to negatively regulate the product of phosphoinositide-3 kinase (PI3K), phosphatidylinositol-3.4,5-trisphosphate. SHIP-1 can be recruited to a large number of inhibitory receptors expressed on natural killer (NK) cells. However, its role in NK cell development, maturation, and functions is not well defined. In this study, we found that the absence of SHIP-1 results in a loss of peripheral NK cells. However, using chimeric mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 50 publications
2
27
1
Order By: Relevance
“…2B). In keeping with the involvement of SHIP-1 in multiple inhibitory pathways (15,27,28), this effect was observed whether HeLa cells expressed SLAMF7 or not. Nonetheless, calculation of the extent of inhibition conferred by expression of SLAMF7 on targets showed that SLAMF7-mediated inhibition was attenuated by loss of SHIP-1 (Fig.…”
Section: Slamf7mentioning
confidence: 73%
“…2B). In keeping with the involvement of SHIP-1 in multiple inhibitory pathways (15,27,28), this effect was observed whether HeLa cells expressed SLAMF7 or not. Nonetheless, calculation of the extent of inhibition conferred by expression of SLAMF7 on targets showed that SLAMF7-mediated inhibition was attenuated by loss of SHIP-1 (Fig.…”
Section: Slamf7mentioning
confidence: 73%
“…SHIP1-deleted mice have severe immune deficiency due to aberrations in the expression of NK cell receptors or downstream signaling (29). A recent study showed that SHIP1 is required for the transition from immature to mature NK cells (39). Generally, hydrolysis of PI(3,4,5)P 3 impairs the recruitment of PH domain-containing kinases to the plasma membrane, resulting in inhibition of PI3K signaling.…”
Section: Discussionmentioning
confidence: 99%
“…4,41,44 A new study suggests that SHIP-1 may control NK cell development and function through combined NK cell-intrinsic and -extrinsic mechanisms. 45 Despite similar Akt hyperactivity in NK cells ( Figure 7C-D), ItpkB Ϫ/Ϫ mice show contrasting reduced mature NK cell numbers, increased NKG2A/C/E/CD94, seemingly unaltered Ly49A, NKG2D, NKp46, and 2B4 but reduced Ly49D/H representation, and the aforementioned hyperactivity and ␥IFN overproduction (Figures 1-7 and supplemental Figures 3-5). It remains to be determined whether these profound differences from SHIP1 Ϫ/Ϫ mice reflect differing increases in cellular PIP 3 activity or impaired specific IP 4 functions unrelated to PIP 3 inhibition 33 in ItpkB Ϫ/Ϫ but not SHIP1 Ϫ/Ϫ NK cells or perturbed positive functions of the SHIP-product PI(3,4)P 2 4,33 in SHIP1 Ϫ/Ϫ but not ItpkB Ϫ/Ϫ NK cells.…”
Section: Soluble Ip4 Limits Nk Cell Effector Functionsmentioning
confidence: 84%